La inserción escolar de los migrantes internacionales en México, 2020 - Vargas Valle, Eunice D. (El Colegio de México, 2023)
Based on the 2020 Mexican Population Census, we analyzed the school insertion of recent child migrants from the United States and the Northern Triangle of Central America and their associated factors. To this end, descriptive statistics and multinomial logistic regression models were used. Both types of international migrants have higher school absenteeism and grade repetition rates than non-migrants, with those for Central American migrants being much higher than for those from the United States. The low economic status and parental schooling of Central Americans, as well as the absence of parents in the home among both Central American and US migrants constitute risk factors for school dropout and discontinuity.